The relationship between the NBA Draft Combine tests, advanced performance metrics, and perceived performance in National Collegiate Athletic Association Division I men`s basketball - Cleary, A.; Winchester, J. B.; Cochrane-Snyman, K. C.; McBride, J. M. (The Journal of Strength and Conditioning Research, 2026)
The NBA Draft Combine (NBADC) assesses an athlete's size, length, and athleticism. Advanced metrics such as player efficiency rating (PER) and Win Share/40 (WS/40) quantify basketball performance. This study explored relationships between NBADC metrics, performance metrics, and perceived performance in a National Collegiate Athletic Association DI Men's Basketball team. Thirteen scholarship athletes (age 20.1 ± 0.64 years, height 1.9 ± 0.1 m, mass 93.9 ± 10.9 kg) participated. Players and coaches ranked each player at their position, creating perceived performance rankings (player rank [PR] and coaches rank [CR]). A Spearman's rank correlation was performed using PER, WS/40, PR, and CR as dependent variables, with anthropometric and physical data as independent variables. Statistical significance was set a priori <=0.05. Stepwise linear regression identified predictive relationships. Win Share/40 significantly correlated with maximum vertical jump (MVJ) (Rho = 0.589, p <= 0.05). Maximum vertical jump explained 35% of WS/40 variability, and MVJ with body composition (BC) predicted 61.4%. Player efficiency rating and raw no-step vertical jump predicted 87.4% of WS/40. Coaches rank and standing reach explained 73.9% of WS/40, while CR alone explained 64.1% of PER. Results suggest lower body muscular power and body composition significantly relate to basketball performance. Coaches assessing players and projecting future contributions should prioritize vertical jump metrics and body composition over other NBADC assessments.